2012
DOI: 10.1017/s0317167100012683
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Alters Tactile Perception in Parkinson's Disease

Abstract: . Contexte : Le traitement anormal de l'information somatosensitive pourrait contribuer à l'altération de la motricité observée dans la maladie de Parkinson (MP). Il a été démontré que les médicaments dopaminergiques modifient le traitement de l'information somatosensitive de telle sorte que la perception tactile en est améliorée. Dans la MP, nous ne savons pas si la séquence temporelle des stimuli tactiles est modifiée et si les médicaments dopaminergiques modifient cette perception. Méthode : La perception t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 33 publications
(56 reference statements)
3
25
0
Order By: Relevance
“…In TOJ tasks, however, motor components do not interfere with the execution of the task, as response speed is not important; only accuracy is taken into account. For this reason, we can conclude that our results involve only perception, not action, suggesting that the basal ganglia play a role in time perception on the scale of milliseconds and corroborating previous findings (Fiorio et al, 2006(Fiorio et al, , 2008Conte et al, 2013;Nelson et al, 2012). The fact that our patients were in the early stages of PD, which are characterized by lesions in the nigrostriatal dopaminergic system, also implicates the basal ganglia in time perception; in the late stages of the disease, several cortical structures (Braak et al, 2003) and other neurotransmitters may be affected (Zgaljardic, Foldi, & Borod, 2004).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In TOJ tasks, however, motor components do not interfere with the execution of the task, as response speed is not important; only accuracy is taken into account. For this reason, we can conclude that our results involve only perception, not action, suggesting that the basal ganglia play a role in time perception on the scale of milliseconds and corroborating previous findings (Fiorio et al, 2006(Fiorio et al, , 2008Conte et al, 2013;Nelson et al, 2012). The fact that our patients were in the early stages of PD, which are characterized by lesions in the nigrostriatal dopaminergic system, also implicates the basal ganglia in time perception; in the late stages of the disease, several cortical structures (Braak et al, 2003) and other neurotransmitters may be affected (Zgaljardic, Foldi, & Borod, 2004).…”
Section: Discussionsupporting
confidence: 92%
“…have measured TOJ resolution of tactile stimuli in young participants, healthy elderly participants, and PD patients, and found that aging, but not PD, reduced it, which led them to conclude dopaminergic systems do not play an role in tactile TOJ. An earlier study had also found that TOJ of tactile stimuli was normal in PD patients (Nelson et al, 2012). In a review about somatosensory abnormalities in PD, though, Conte et al (2013) pointed out that "although tactile abnormalities are not clinically evident in PD, a large body of evidence indicates altered tactile information processing in both spatial and temporal domains".…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While declines in olfactory and visual function are well documented in PD [3,4], deficits in other sensory systems are less so, and most studies have evaluated medicated PD patients of relatively advanced stage. In the case of somatosensation, PD-related decrements in spatial discrimination [5,6], temporal processing [7,8], and haptic perception [9,10] are reasonably well established. However, this is not the case for point pressure sensitivity (PPS), a measure of myelinated Aβ fiber function mediated through Merkel and Meissner mechanoreceptors [11][12][13].…”
Section: Introductionmentioning
confidence: 94%
“…Aberrations in somatotopy also exist in FHD indicating reduced inter-digit spacing and abnormalities in the topographic ordering [50][51][52]. In addition to FHD, alterations in touch perception in Parkinson's disease [53,54], abnormal sensory gating in Tourette's [55], and reduced SAI sensorimotor circuitry in restless legs syndrome [56] all provide evidence for a role for somatosensory processing in the control of movement. We refer the reader to excellent in-depth reviews detailing somatosensory abnormalities in movement disorders [57,58].…”
Section: In Uence Of Somatosensory Cortex On Motor Behaviormentioning
confidence: 99%